BEHAVİOURAL FİNANCE: AN EXPLORATORY REVİEW - A.O. Adaramola; P.A. Kayode; O.V. Adewale; O.F. Ogiamien (Хабаршысы. Экономика сериясы, 2022)
The belief that investors care about utilitarian, rationality, cognitive errors and self-control charac-teristics by the traditional financial theories have been challenged in the literature over the years by the behavioural financial theories as being unrealistic. To the latter, investors are more often than not, sub-jected to self-deception, social influence, emotion and heuristic simplification decision-making biases in real life situations. Therefore, behavioural finance uses the influence of psychology to explain the behav-iour of investors. For a better understanding of this approach, this paper presents an exploratory survey of the concepts and theoretical underpinnings with respect to behavioural finance. Methodically, this study traces the foundational theories in financial decision and evolving behavioural finance theories. Our review brings to the fore the gap between traditional finance theories and real-life situations which accommodates human aspects in decision making. Amidst the perceived several biases that may ac-company human behaviour as it affects financial decisions, we find that both traditional and behavioural finance theories are essential for informed financial decisions. We advocate a synchronization of the two theoretical leanings in taking investment decisions as standalone approach of any of these two will lead to sub-optimal investment decisions.